PEMERANAN TOKOH SYLVIA DALAM NASKAH THE TYPISTS KARYA MURRAY SCHISGAL TERJEMAHAN YURI AKHMAD S - subekti, galuh (Tonil: Jurnal Kajian Sastra, Teater dan Sinema, 2017)
Modern man has now undergone a change of perspective with various problems concerning individuals and even groups. The reason is so complex, with the current pace of modern man more follow the actual desire is not the choice. Humans assume that he is alright without realizing that he has become an object and experiencing non-existence. Today's modern man has unknowingly experienced and felt the void, hope, loneliness, and anxiety. Since Sylvia young to old Sylvia many changes. Awareness as a manuisa who lost existence is supported by the presence of Paul. Staging will be presented with the concept of pantomime and realist acting style. With so actors are required to be able to combine the concept with the achievement as much as possible. Key word : Theatre, actor, Syvia, acting, physical theatre, pantomime.